The real effects of banking supervision: evidence from enforcement actions - Danisewicz, Piotr; McGowan, Danny; Onali, Enrico; Schaeck, Klaus (Elsevier, 2016)
We present a novel way to examine macro-financial linkages by focusing on the real effects of bank supervisors’ enforcement actions. Exploiting plausibly exogenous variation in supervisory monitoring intensity, we show that enforcement actions in single-market banks trigger temporarily large adverse effects for the macroeconomy by reducing personal income growth, the number of establishments, and increasing unemployment. These effects are related to contractions in bank lending and liquidity creation, and are more pronounced when we consider enforcement actions on both single-market and multi-market banks, and in counties with fewer banks and greater external financial dependence.